The Level of Parental Education in Relation to The Upbringing of Children: An analytical descriptive study - Kameran Jewher Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The study aims to clarify the relationship between the level of parental education and raising children, to know the role of the level of parental education in shaping the child’s personality, and also know the role of the level of parental education in choosing the appropriate style of education for the child. In this study, the researcher used the descriptive-analytical method to reveal the relationship between the independent variable (parents’ education level) and the dependent variable (children’s education, the formation of the child’s personality, and the selection of the appropriate method or style of education for the child). Among the most important results of this study: It was found that there is a relationship between the level of education of the parents and the upbringing of the children. The level of parental education has an effective role in building and forming the successful personality of the child. The high level of education of parents leads to compatibility and agreement in their educational attitude towards children.